Comparative Analysis of The 2013 Curriculum and The Merdeka Curriculum for Civic Education - Suriaman Suriaman; Nisrina Nurul Insani; Aim Abdulkarim; T Heru Nurgiansah; Muhammad Asriadi (CV. Rayyan Dwi Bharata, 2025)
The pandemic has resulted in a learning crisis, demanding a curriculum change. A comparative analysis between the 2013 Curriculum and the Merdeka Curriculum at the Secondary School level in civic education becomes relevant to evaluate the education system's response to these challenges. This research aims to identify the differences and similarities in the approaches of both curricula towards civic education and understand their potential in addressing potential learning disparities and inequalities arising from the pandemic. Focusing on the values of Pancasila and intracurricular learning, this study provides profound insights into the adaptability and effectiveness of the curriculum during a crisis. The results are expected to offer guidance for the development of a responsive and inclusive curriculum in facing the dynamics of learning amid global challenges.